Importância do gerenciamento com base em dados estudo de caso : farmácias de manipulação do Estado do Rio Grande do Norte - Calle, Juan Javier Alarcon (2009)
Last century Six Sigma Strategy has been the focus of study for many scientists, between the discoveries we have the importance of data process for the free of error product manufactory. So, this work focuses on data quality importance in an enterprise. For this, a descriptive-exploratory study of seventeen pharmacies of manipulations from Rio Grande do Norte was undertaken with the objective to be able to create a base structure model to classify enterprises according to their data bases. Therefore, statistical methods such as cluster and discriminant analyses were used applied to a questionnaire built for this specific study. Data collection identified four group showing strong and weak characteristics for each group and that are differentiated from each other